The solitary wave solutions to the Klein-Gordon-Zakharov equations by extended rational methods - Yao, Shao-Wen; Zekavatmand, Sayyed Masood; Rezazadeh, Hadi; Vahidi, Javad; Ghaemi, Mohammad Bagher; İnç, Mustafa (Aip Publishing, 2021)
In this paper, using the extended rational sine-cosine and rational sinh-cosh methods, we find new soliton solutions for the Klein-Gordon-Zakharov equations. The extended rational sine-cosine and rational sinh-cosh methods are prospering in finding soliton solutions of the Klein-Gordon-Zakharov equations. By means of these methods, we found some young solitons of the above mentioned equation. The conclusions we receive are dark, bright, and periodic. In addition, in order to imagine the underlying dynamics of the obtained soliton solutions, 2D and 3D plots are drawn.
Keywords: Model; Evolution